Des terrains incomparés ? - Marie David (Terrains/Théories)
What can be learned from observing, in the same survey, fields and cases that are usually separately studied? What is the heuristic value of this comparison? This article proposes to answer these questions through the example of a sociological study of knowledge in educational institutions.In a field survey, I simultaneously observed the transmission of knowledge in two different educational institutions (high school and university), and in three disciplines belonging to two distinct disciplinary fields (sociology on the one hand, physics and chemistry on the other). The choice of these comparisons obeys the following initial question: is the process of knowledge transmission for a given discipline and form of schooling specific? Chicago's interactionist theoretical perspective encourages the comparison of dissimilar cases in order to produce research that questions administrative and common-sense categories. In this article I present how, from this perspective, I selected the cases to be studied, how I analysed them, and some of the results that came out of this investigation. I also show how the survey could be extended to include cases that are even more remote.